Migration and Opera Old and New : Repertoire Revivals and Eva Noer Kondrup’s Den Rejsende - Severn, John R (Nordic Theatre Studies, 2023)
This article uses Eva Noer Kondrup’s chamber opera Den Rejsende (Copenhagen 2018) to examine the challenges and opportunities provoked by the operatic form when attempting to create socially responsible theatre. Focusing on how opera reflects and contributes to contemporary discourse on migration, it examines how opera’s unusual performance and reception demands differentiate it from, for example, spoken verbatim theatre. The article first considers the most common way opera companies today engage with migration – through productions of existing operas – in which socially responsible decisions are primarily in the hands of directors and designers and relate mostly to interpretation, and it explores some of the risks and opportunities of engaging with migration in recent revivals of repertoire works. It then analyses how questions of social responsibility in new operas extend to structural issues that are the field of the composer and librettist. The article examines Kondrup’s decisions as librettist-composer of Den Rejsende, demonstrating the potential for opera to use non-realist operatic techniques to engage with some of the issues with which spoken verbatim theatre has wrestled, including questions of authority, authenticity and authorship, and of empathy, engagement, and identification. The production, performed by two Swedish singers from non-refugee backgrounds in multiple roles, favoured distanciation techniques over “authenticity effects” and avoided tensions between giving voice to and speaking for contemporary refugees that can arise in spoken verbatim theatre. While the libretto contained found text, this was from historical refugee situations, and from the words of Inger Støjberg in her role as Danish Minister for Immigration, Integration and Housing. By throwing a spotlight on the words of an elected representative, Den Rejsende indicated an area in which audience members of what is often thought of as an affective theatrical form might have some influence in effecting practical change.